FROM KARGIL TO COMPOSITE DIALOGUE: INDIA-PAKISTAN RELATIONS UNDER GENERAL MUSHARRAF’S LEADERSHIP AND ITS EVOLVING LEGACY IN THE CONTEMPORARY GEO-POLITICAL PERSPECTIVE - Muhammad Tahir; Asad Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper examines the evolution of India-Pakistan relations under General Pervez Musharraf's leadership, with a focus on key events from the Kargil conflict (1999) to the Composite Dialogue process initiated in 2004. Spanning the period from 1999 to 2008, the study explores the complexities of political, military, and diplomatic engagements between the two nations, highlighting pivotal moments such as the Kargil War and the Agra Summit. It delves into critical issues like the Siachen dispute, terrorism-related tensions post-2001, and the efforts toward normalization through backchannel diplomacy and people-to-people exchanges. Furthermore, the paper investigates how Musharraf's strategic leadership and peace initiatives, particularly the Composite Dialogue, shaped bilateral relations, aiming to resolve long-standing conflicts. The research also assesses the enduring legacy of these policies in contemporary geopolitics, analyzing their implications for the current state of India-Pakistan relations. Through a combination of qualitative and descriptive approaches, this study provides a comprehensive analysis of the challenges and diplomatic breakthroughs that defined this crucial phase in South Asian politics. The findings contribute to understanding the lasting impact of Musharraf's policies on the evolving dynamics of India-Pakistan relations.